Towards explaining spatial touch perception: Weighted integration of multiple location codes. Issue 1 (17th February 2016) - Badde, Stephanie; Heed, Tobias
ABSTRACT: Touch is bound to the skin – that is, to the boundaries of the body. Yet, the activity of neurons in primary somatosensory cortex just mirrors the spatial distribution of the sensors across the skin. To determine the location of a tactile stimulus on the body, the body's spatial layout must be considered. Moreover, to relate touch to the external world, body posture has to be evaluated. In this review, we argue that posture is incorporated, by default, for any tactile stimulus. However, the relevance of the external location and, thus, its expression in behaviour, depends on various sensory and cognitive factors. Together, these factors imply that an external representation of touch dominates over the skin-based, anatomical when our focus is on the world rather than on our own body. We conclude that touch localization is a reconstructive process that is adjusted to the context while maintaining all available spatial information.